Constipation and Aroma Massage in Elderly Individuals - Diğdem LAFÇI (Bezmiâlem Science, 2020)

(untitled)
Constipation is a gastrointestinal motility disorder characterized by decreased bowel movements or difficulty in the defecation process. In the first step of non-pharmacological measures in constipation management, it is generally recommended to increase regular physical activity, and fluid and fiber consumption. In the medical treatment of chronic costipation; suppositories, laxatives and enemas are used. However, the long-term use of some laxatives can cause increased constipation and harmful side effects, including fecal impaction. Abdominal aroma massage is an inexpensive, noninvasive method that can be applied by nurses for the treatment of constipation. It can also be done by the patient himself/herself. Studies have shown that abdominal aroma massage stimulates peristalsis , shortens the colon transit time, increases the frequency of bowel movements, and reduces the accompanying feelings of pain and discomfort and the incidence of defecation in constipated patients. Abdominal effleurage, petrissage, kneading, vibration, and tapotement are thought to reduce muscle tension, increase local circulation, reduce indigestion, stimulate stomach acid secretion, increase appetite, stimulate peristalsis, alleviate constipation and reduce high blood pressure. In this article, the use and effects of abdominal aroma massage in constipation management will be explained.